Setting research priorities for effective management of a threatened ecosystem: Australian alpine and subalpine peatland. Issue 3 (1st February 2023) - Rowland, Jessica A.; Walsh, Jessica C.; Beitzel, Matthew; Brawata, Renee; Brown, Daniel; Chalmers, Linden; Evans, Lisa; Eyles, Kathryn; Gibbs, Rob; Grover, Samantha; Grundy, Shane; Harris, Rebecca M. B.; et al.
Abstract: Threatened ecosystem conservation requires an understanding of the effectiveness of management and the challenges hindering successful protection and recovery. Bringing together researchers, land managers and policymakers to identify key threats, management needs, and knowledge gaps provides a unified account of the evidence and tools needed to improve threatened ecosystem management. We undertook a research prioritization process for Australian alpine and subalpine peatlands with experts across policy, research, and management. Through individual interviews, structured group discussions, and voting, we generated 25 priority research questions that, if addressed, would enhance our capacity to conserve peatlands. Knowledge gaps spanned four topics: understanding peatland dynamics, impacts of threats, methods to manage these, and the effectiveness of management. Consistent monitoring standards, an open‐access knowledge platform and commitment to long‐term joint research and management were identified as vital. This collaboration enabled development of a shared agenda of research priorities to target knowledge gaps for informing policy and management of threatened alpine peatlands. Our findings substantiate the importance of stronger ongoing collaboration among researchers, land managers and policymakers across jurisdictions to support conservation.